MEMBUAT TOKO ONLINE DENGAN GOOGLE SITES - Endar Nirmala; Sri Mulyati; Ari Mulyoto (Abdi Jurnal Publikasi, 2024)
Digital Business is one of the subjects in the marketing skills program. This subject contains the competencies used for a career in today's industrial world, whether working for another party, being an independent entrepreneur, or as a provision for continuing education according to one's vocation. Apart from that, this subject contributes to supporting the competencies of graduates who will have careers in the fields of digital entrepreneur, content writer, social media specialist, digital marketing, merchandising staff, online customer service, and purchasing staff. To support this career, students must be competent in the fields of business economics and general administration, marketing, business planning, business communication, digital branding, digital onboarding, digital marketing, and digital operations. Learning can use various approaches, strategies, models and methods that are in accordance with the characteristics of the competencies that must be learned so that it can create learning that is interactive, inspiring, fun, challenging, motivates students to participate actively, and provides sufficient space for initiative, creativity, independence in accordance with students' talents, interests, passions, and physical and psychological development. Creating an online shop is one activity that can help develop students' creativity in exploring digital business. To create an online shop, there are several applications that can be easily used, including using a blog, using an e-commerce application, or creating your own online shop website and Google Sites. In community service activities at SMK Letris Indonesia 2, students will be trained to create an online shop using Google Sites. This is motivated by market potential and e-commerce growth, market gaps or specific customer needs, student skills development, technological innovation, growth of small and medium businesses and increased access to education and training. Google Sites is a service from Google that allows users to easily create websites without requiring complex coding or web design skills. Google Sites is designed to be an easy-to-use platform, making it suitable for beginners and users with no web design experience. Google Sites is integrated with various other Google services, such as Google Drive, Google Calendar, and Google Forms. It facilitates collaboration, easy content management, automatic updates, available templates and is free for google users. The ultimate goal of creating an online shop with Google Sites will help students to improve their competence in digital business and build an entrepreneurial attitude. In conclusion, community service in creating an online shop with Google Sites helps in building an entrepreneurial attitude to increase competence in digital business, but participants still need development, especially those related to important factors in creating a website.